The Influence of pH Values on the Crystallite Size of ZnO by Solvothermal Synthesis - Ahmadi Jaya Permana; Dian Wulandari; Hartati Hartati; Harsasi Setyawati; Mochammad Zakki Fahmi (Universitas Airlangga, 2017)
Zinc oxide (ZnO) is a semiconductor material that widely used in various applications due to its unique properties. Synthesis of ZnO by solvothermal method has been conducted with controlled pH values. The variations of pH value were 10, 11 and 12 by adjusting NaOH content. Crystall structure of the synthesis products after heat treatment at 110oC and 600oC has characterised by X-ray Diffratometer (XRD). Crystallite size of ZnO was measured by Scherrer equation. Crystall phase of ZnO has been observed on all pH value variations at 110 oC with 22,98-37,06 nm of crystallite size, whereas ZnO has been observed on all pH value variations at 600 oC with 41,39-71,77 nm of crystallite size.Keywords: ZnO, pH values, crystallite size, solvothermal